Memastikan Efektivitas Implementasi Kebijakan Publik - Yosep Gede Sutmasa (Universitas Mahendradatta Denpasar, 2021)
No matter how good the formulation of a public policy is, if it fails to be implemented then the policy is useless. Policy implementation is one of the determinant sequences in the entire public policy process, because it is directly related to the performance of a policy, the realization of goals and results (outputs and outcomes). Therefore, ensuring the effectiveness of public policy implementation is very important, that is, first of all by properly and correctly understanding the entire process of public policy, especially the factors that influence policy implementation. Some of the influencing factors are: size and policy objectives, resources, characteristics of implementing agents, attitudes / tendencies (disposition) of operators, communication, economic, social and political environment, whether the problems are easy or not, the ability of policies to structure implementation appropriately. Second, oversee the implementation of public policies with full responsibility through monitoring, evaluation and reward.